Technocrats and the forging of technocratic (or not) networks in Iberian dictatorships (Tempo e Argumento, 2022)
This article examines the reception of theories on growth and development in Iberian dictatorships and their political repercussions as the basis of reformist projects of a technocratic tradition that sought to provide unusual sources of legitimacy to authoritarian regimes in order to ensure the preservation of their substantive principles. Under the leadership of the Portuguese man Marcello Caetano and the Spanish man Laureano López Rodó, the implementation of these projects has been addressed through the lens of networks of friends and collaborators selected as experts. These networks brought together people of various political and ideological sensitivities and, although they have helped to strengthen the position of their respective sponsors in hard core power, they did not necessarily share ideological views and political purposes. This is addressed from a comparative and transnational perspective, to the extent that the comparative exercise allows us to identify the similarities and differences between the cases in Spain and Portugal, while the transnational focus helps us to analyze them altogether.Keywords: Iberian dictatorships; technocracy; power networks.